2019
DOI: 10.9782/16-00044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Between Teacher Training and Support Strategies for Students Utilizing Augmentative and Alternate Communication

Abstract: Schools in the United States support a large group of students requiring the assistance of augmentative and alternate communication (AAC). It is currently unknown what types of training and supports special education teachers require or are receiving to meet the needs of these students. A convenience sample of 3,200 teachers was surveyed about the following topics: (a) number and description of students who do not have a proficient way of communicating, (b) the efforts employed by teachers to support AAC adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…IDEA (2004) identifies AT as a device or service that includes “training or technical assistance for such child…and…for professionals” (p. 6). Both students and teachers must have training with the AT to successfully use the devices (Andzik et al, 2019).…”
Section: Framework For At In Inclusive Classroomsmentioning
confidence: 99%
“…IDEA (2004) identifies AT as a device or service that includes “training or technical assistance for such child…and…for professionals” (p. 6). Both students and teachers must have training with the AT to successfully use the devices (Andzik et al, 2019).…”
Section: Framework For At In Inclusive Classroomsmentioning
confidence: 99%
“…In this regard, Nayir and Saridas [51] concluded that teachers who develop an innovative behavior or trait in their activities related to their teaching performance in class sessions will achieve a regulatory effect in terms of cultural values. Andzik et al [52] point out that there is a statistically significant association between the professional traits of the teacher linked to the amount of training he acquired with his ability to communicate with his students, that is, teachers with greater mastery will have to develop various didactic support strategies for their students around their communication. In the same line of results, Amiruddin and Jannah [53] concluded that teachers who use an appropriate communication style will build conditions for class sessions to provide significant contributions to the students' acquisition of knowledge.…”
Section: Results Of Inferential Analysis and Discussionmentioning
confidence: 99%
“…The fact that students with complex communication needs present heterogeneous characteristics (Light & McNaughton, 2012) implies that professionals will need to stay current in their practices to ensure effective instruction for all students (Lund et al, 2017). The combination of limited research on the decision-making during AAC assessment (Lund et al, 2017; Schlosser & Raghavendra, 2004), the lack of teacher training (Andzik et al, 2019; Costigan & Light, 2010; Da Fonte et al, 2022 accepted), and the rapid changes in assistive technology (Abbot & Bride, 2014) highlights the need for having (a) a reliable, systematic, and comprehensive approach in identifying communication systems; (b) practitioner-friendly assessment tools that are grounded in the literature; (c) a collaborative team approach for systematically identifying and supporting the needs of students with complex communication; and (d) AAC training across all disciplines. As such, it is critical to conduct comprehensive assessments in a collaborative manner when identifying a communication system for students with complex communication needs (Brady et al, 2016; Lund et al, 2017) to maximize the strengths of each team member.…”
Section: Discussionmentioning
confidence: 99%